Peran Guru Pendidikan Agama Islam dalam Menumbuhkan Kesadaran Etika Digital Siswa di MTs Muhammadiyah Bandung Tulungagung - Meidi Sapriansyah; M. Riza Zainuddin (CV. ALIM'SPUBLISHING, 2026)
The rapid development of digital technology has transformed students’ communication, access to information, and social interactions. However, the growing use of digital media has also created ethical challenges, including the spread of misinformation, irresponsible social media use, and declining politeness in online communication. In response to these issues, Islamic Religious Education (IRE) teachers play a vital role in fostering students’ digital ethics by integrating Islamic values into the learning process. This study aims to examine the role of IRE teachers in developing students’ digital ethical awareness at MTs Muhammadiyah Bandung Tulungagung. A qualitative case study approach was employed, with data collected through observations, interviews, and documentation involving the principal, IRE teachers, and students. Data were analyzed using an interactive model, while credibility was ensured through source and technique triangulation. The findings show that IRE teachers effectively promote digital ethics through exemplary behavior, moral guidance, classroom instruction, supervision of students’ digital activities, and encouragement of respectful online communication. These efforts enhance students’ awareness of responsible technology use, ethical communication, critical evaluation of digital information, and the application of Islamic values in digital interactions. The study concludes that strengthening the pedagogical competence and exemplary role of IRE teachers is essential for fostering an ethical digital culture and reinforcing students’ character education in the digital era.